Hematological and Biochemical Parameters of Subadult Captive Siberian Tigers (Panthera tigris altaica) - Xin Liu; Izhar Hyder Qazi; Haijun Wang; Zhiqiang Han; Xiao Li; Xiuli Zhang; Rui Du; Naiquan Yao; Chao Xu (Animals)
The conservation of Siberian tigers, the apex predators in the Asia–Pacific region, hinges on a thorough understanding of their physiological statuses and adaptive mechanisms. In order to fill a critical gap in our knowledge of this endangered species, we conducted comprehensive analyses of Siberian tiger whole blood and serum using modern hematology and biochemical analyzers. The blood samples were collected from subadult (2–3 years old) Siberian tigers (n = 15 for hematological analysis and n = 7 for biochemical analysis). In the present study, distinct hematological patterns including an elevated mean platelet volume (MPV) and a higher red cell distribution width coefficient of variation (RDW-CV) were observed, which were possibly triggered by pre-anesthesia resistance movements. Notably, the neutrophil percentage in Siberian tigers was found to be significantly higher than that in domestic cats and Bengal tigers, suggesting species-specific immune adaptations. In addition, serum biochemical analysis provided refined parameter ranges for subadult tigers. Unlike previous studies encompassing a broader age range, our data specifically characterize biochemical profiles in subadult tigers, offering vital baselines for health monitoring and conservation strategies. These results not only enhance our understanding of the biology of Siberian tigers but also provide scientific support for targeted conservation efforts, fostering population recovery and ecological balance in their natural habitats.